2017
DOI: 10.1097/md.0000000000006466
|View full text |Cite
|
Sign up to set email alerts
|

Association between pet ownership and coronary artery disease in a Chinese population

Abstract: A number of studies have suggested the benefits of pet ownership to human health, including cardiovascular disease (CVD). However, there are few findings regarding pet ownership and coronary artery disease (CAD). The objective of this study is to investigate the association between pet ownership and CAD in a Chinese population. From October 2015 to May 2016, a survey consisting of 561 consecutive patients was done in Nanjing, China. Based on the results of coronary arteriography for the first time, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Fig 1 illustrates the search process. A total of 12 cohort studies were included for our systematic review[810, 16–24]. The characteristics of these studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig 1 illustrates the search process. A total of 12 cohort studies were included for our systematic review[810, 16–24]. The characteristics of these studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were conducted in North America, Europe, and Australia. Only one was conducted in China[16]. Dogs and cats were the most common pet animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, systolic and diastolic blood pressures were found to be significantly lower in the home environment in couples who owned a pet than those who did not (Allen, Blascovich, & Mendes, 2002). More recently, an online study highlighted a lower risk of self-reported hypertension in dog owners than non-owners (Lentino, Visek, McDonnell, & DiPietro, 2012), while a study on Chinese patients revealed a protective factor of pet ownership, and notably dog ownership, for CVD (Zhi-Yong et al, 2017). More specific to the elderly population, Friedmann et al (2013) reported that the mere presence of a pet, and in particular a dog, improved ambulatory blood pressure in older (50-83 years) adults with hypertension.…”
Section: Pets and Cardiovascular Healthmentioning
confidence: 98%
“…Early life lung function is critical for respiratory health throughout life Among several environmental determinants in early life that may affect early life lung function, rising rates of pet ownership globally have stimulated our interest to perform a study on the impact of household pets. According to a report in 2015, pet ownership increased by 54.2% since 2009 in China compared to the global pet ownership which increased by 24.0% . In such circumstance, the relationships between early pet ownership on asthma and allergies have been extensively studied, and its impact on early life lung function has not received the same attention.…”
Section: Introductionmentioning
confidence: 99%